Issues in the Impacts of Climate Variability and Change on Agriculture 2003
DOI: 10.1007/978-94-017-1984-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Modeling of the Effects of Large-Scale Circulation on Daily Weather in the Southeastern U.S.

Abstract: Abstract. Statistical methodology is devised to model time series of daily weather at individual locations in the southeastern U.S. conditional on patterns in large-scale atmosphere-ocean circulation. In this way, weather information on an appropriate temporal and spatial scale for input to crop-climate models can be generated, consistent with the relationship between circulation and temporally and/or spatially aggregated climate data (an exercise sometimes termed 'downscaling'). The Bermuda High, a subtropica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 39 publications
1
56
0
1
Order By: Relevance
“…The summer mean location of the Bermuda high also is significantly related to warmseason drought variability in the Southeast via its influence on moisture advection into the region (Stahle and Cleaveland 1993;Katz et al 2003;Diem 2006;Ortegren et al 2011). AMO1 is associated with increased drought frequency in the Atlantic coastal Southeast (Enfield et al 2001;McCabe et al 2004).…”
Section: B Interdecadal Drought Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The summer mean location of the Bermuda high also is significantly related to warmseason drought variability in the Southeast via its influence on moisture advection into the region (Stahle and Cleaveland 1993;Katz et al 2003;Diem 2006;Ortegren et al 2011). AMO1 is associated with increased drought frequency in the Atlantic coastal Southeast (Enfield et al 2001;McCabe et al 2004).…”
Section: B Interdecadal Drought Variabilitymentioning
confidence: 99%
“…The NAO influences the tracks of TCs over the North Atlantic Ocean (Elsner and Kara 1999;Elsner and Kocher 2000;Keim et al 2004;Elsner et al 2006;Elsner and Jagger 2006;Dailey et al 2009). Additionally, there is evidence of reductions in winter precipitation in the southeastern United States during NAO2 phases (Stenseth et al 2002), although some studies indicate an insignificant relationship between the NAO and precipitation in the southeastern United States during other seasons (Stahle and Cleaveland 1992;Henderson and Vega 1996;Katz et al 2003;Tootle et al 2005;Hurrell and Deser 2009). Maxwell et al (2012) identified the NAO as the only significant variable affecting the likelihood of a TCDB impacting the southeast ACS during the period 1950-2008.…”
Section: A Interdecadal Tc Landfall and Tc Precipitation Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter case, c(t) is called a covariate (Coles, 2001;Katz et al, 2003). These new parameters, µ 0 and a µ (or the corresponding parameters for σ and ξ ), can be estimated in the same way as µ, σ and ξ using Equation 5.…”
Section: Maximum Likelihood Estimationmentioning
confidence: 99%
“…The parametric (harmonic) form of the model reduces the uncertainty of the parameter estimates. This approach is based on a more general method described in Coles (2001) and Katz et al (2003), who include external influences as covariates in their extreme-value analysis. We analyse a set of 689 rain gauge records across the UK, revealing coherent spatial patterns of extreme precipitation characteristics and their annual cycle.…”
Section: Introductionmentioning
confidence: 99%